Improving Studentsâ Writing Achievement Through Peer Review And Facebook For Grade XI of SMA Negeri 2 Singaraja - Lestari, L.D.K. (Journal of Education Action Research, 2017)
This research aimed at improving studentsâ writing achievement for grade X in SMA Negeri 2 Singaraja through peer review and Facebook. In the planning step were carried out to create a Facebook group and make lesson plans. The results of the research showed as follows: First, there is a positive trend of the studentsâ mean score.Â  It increased from 64.9 in the pre test to 77.9 in the first cycle and to 88.7. Second, there were no students left behind in the second cycle. In pre test, there were 26 students who did not passed the passing grade of 72. In the first cycle, the number decreased to 4 and finally all studentsâ score had passed the passing grade after the second cycle. Third, the studentsâ response toward the implementation of the technique is positive. This means that the third indicator of research success had also been accomplished.Â